2019
DOI: 10.1002/tl.20368
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence and Positive Education: Preparing Students for a Better Tomorrow

Abstract: This chapter discusses the importance of emotional intelligence and presents a case for including emotional intelligence in positive education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
3
0
3
Order By: Relevance
“…Emotions involve physiological, cognitive, and social processes (Izard 2009). The discipline of psychology initially adopted a disorder or deficiency-oriented approach, focusing on weaknesses and finding solutions to eliminate them (Anand 2019). Studies have shown that the difference between those who can improve themselves and those who cannot stem from the number of positive emotional experiences (Catalino and Fredrickson 2011).…”
Section: Frederickson's Broaden-and-build Theorymentioning
confidence: 99%
“…Emotions involve physiological, cognitive, and social processes (Izard 2009). The discipline of psychology initially adopted a disorder or deficiency-oriented approach, focusing on weaknesses and finding solutions to eliminate them (Anand 2019). Studies have shown that the difference between those who can improve themselves and those who cannot stem from the number of positive emotional experiences (Catalino and Fredrickson 2011).…”
Section: Frederickson's Broaden-and-build Theorymentioning
confidence: 99%
“…La inteligencia interpersonal son aquellas capacidades que una persona tiene para poder relacionarse por medio de habilidades sociales con los demás (Anand, 2019), teniendo en cuento esto, las maestras entrevistadas hicieron referencia a las siguientes categorías emergentes.…”
Section: Influencia De Las Herramientas Digitales En La Inteligencia Emocional Interpersonalunclassified
“…Ahora, en lo que respecta a la inteligencia emocional se consideran cinco dimensiones tales como: el autoconocimiento, la autorregulación, la motivación, la empatía y las habilidades sociales (Anand, 2019), las cuales se encuentran inmersas en el desarrollo intrapersonal e interpersonal de las personas (Sebastián y Garrido, 2017). De esta manera, se conoce que cada personalidad es distinta, pues los estados de ánimo están en constante cambio encontrando emociones de cólera, tristeza, miedo, inseguridad y desconfianza lo que puede perturbar la personalidad del infante (Sarmento-Henrique et al, 2020).…”
Section: Introductionunclassified
“…Dengan adanya pengajaran positif membuat pengajar dan mahasiswa puas dengan pembelajaran, mampu mengelola stres pribadi, dan memenuhi kebutuhan mahasiswa baru (Dahl et al, 2019). Pengajaran positif juga dapat meningkatkan keterampilan dan pengetahuan, serta menghadapi tantangan akademik (Anand, 2019). Penelitian ini akan fokus mengembangkan pengajaran positif berbasis modul pada mahasiswa baru dalam mata kuliah pengembangan iri Jurusan Psikologi.…”
Section: Pendahuluanunclassified